Venus as a Laboratory for Exoplanetary Science. Issue 8 (28th August 2019) - Kane, Stephen R.; Arney, Giada; Crisp, David; Domagal‐Goldman, Shawn; Glaze, Lori S.; Goldblatt, Colin; Grinspoon, David; Head, James W.; Lenardic, Adrian; Unterborn, Cayman; Way, Michael J.; Zahnle, Kevin J.
Abstract: The current goals of the astrobiology community are focused on developing a framework for the detection of biosignatures, or evidence thereof, on objects inside and outside of our solar system. A fundamental aspect of understanding the limits of habitable environments (surface liquid water) and detectable signatures thereof is the study of where the boundaries of such environments can occur. Such studies provide the basis for understanding how a once inhabitable planet might come to be uninhabitable. The archetype of such a planet is arguably Earth's sibling planet, Venus. Given the need to define the conditions that can rule out bio‐related signatures of exoplanets, Venus provides a unique opportunity to explore the processes that led to a completely uninhabitable environment by our current definition of the term. Here we review the current state of knowledge regarding Venus, particularly in the context of remote‐sensing techniques that are being or will be employed in the search for and characterization of exoplanets. We discuss candidate Venus analogs identified by the Kepler and TESS exoplanet missions and provide an update to exoplanet demographics that can be placed in the potential runaway greenhouse regime where Venus analogs are thought to reside. We list several major outstanding questions regarding the Venus environment and the relevance of those questions to understanding the atmospheres and interior structure of exoplanets. Finally, we outline the path toward a deeper analysis of our sibling planet and the synergy to exoplanetary science. Plain Language Summary: The search for life in the universe requires that we develop a deep understanding of objects inside of our solar system so that we may better interpret data of planets orbiting other stars. A key part of this understanding lies in a comparison between Venus and Earth since they lie at opposite ends of the habitability spectrum. Here we describe the current state of knowledge regarding Venus and the primary outstanding questions related to its interior, atmosphere, and surface conditions. We describe how understanding Venus is directly related to extrasolar planets and why many of the planets being discovered around other stars are likely direct analogs of Venus. We show how studies of Venus will allow an improved definition of the boundaries of planetary habitability and also will reveal important clues as to how Venus and Earth developed dramatically different surface conditions, despite being the same size and with similar starting conditions. Key Points: The characterization of terrestrial exoplanets, including interior structure and atmospheres, is becoming a primary focus of exoplanetary science The boundaries of habitability are best understood through the study of the extreme environments present on Earth and Venus There are many outstanding questions regarding Venus that are critical to answer in order to better constrain models for exoplanets